Self-Report Scale of Adaptation - EDAO-AR: Evidences of Validity - Yoshida, Elisa Medici Pizao (Paidéia (Ribeirão Preto), 2013)
The Scale of Adaptation-Revised (EDAO-R) provides a measure of the adaptive efficacy, understood as the degree of success in coping with the vicissitudes of life. Its assessment is based on clinical interview material. The study aimed at obtaining evidence of the validity of a self-report version of EDAO-R, identified as EDAO-AR. Items were developed to assess the quality of adaptation of two sectors of the personality: Affective-Relational (A-R) and Productivity (Pr). Sample of 237 outpatients and caregivers. We obtained evidence of validity based on internal structure (internal consistency, factor analysis, cluster analysis), and validity based on external variables (relationship between EDAO-AR and the Assessment Symptoms Scale-40/EAS-40). Results showed good internal consistency and three dimensions for both sectors: focus on the problem situation, focus on interpersonal relationships and focus on self. Was obtained, as expected, negative correlations between EDAO-AR and EAS-40. Suggestions were made for the second version of the scale.